11th Annual Congress of the European College of Sport Science (ECSS), Lausanne, Switzerland 5-8 July 2006 - Book of Abstracts (11th Annual Congress of the European College of Sport Science (ECSS), Lausanne, Switzerland 5-8 July 2006 - Book of Abstracts, 2006)
The scientific programme is composed of more than 1.500 abstracts, which were accepted after being carefully reviewed . This year´s Congress is the largest in the history of the ECSS, underlining both the interest of the sport scientific community and the importance of the ECSS as an interdisciplinary forum for ongoing debate. In view of the multifaceted character of sport science, state-of-the-art presentations cover basic and applied sciences as they relate to sport, exercise and health. The presented abstracts comprise not only all relevant sub-disciplines of sport science but also all continents and 68 different nations. The abstracts are distributed among 4 Plenary Sessions, 50 Invited Symposia, 50 Thematic Sessions and 3 Poster Sessions each presenting close to 400 Posters.